2011
DOI: 10.1371/journal.pone.0026107
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Rat Spinal Cord Injury with the Neurotrophic Factor Albumin-Oleic Acid: Translational Application for Paralysis, Spasticity and Pain

Abstract: Sensorimotor dysfunction following incomplete spinal cord injury (iSCI) is often characterized by the debilitating symptoms of paralysis, spasticity and pain, which require treatment with novel pleiotropic pharmacological agents. Previous in vitro studies suggest that Albumin (Alb) and Oleic Acid (OA) may play a role together as an endogenous neurotrophic factor. Although Alb can promote basic recovery of motor function after iSCI, the therapeutic effect of OA or Alb-OA on a known translational measure of SCI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 91 publications
1
52
0
Order By: Relevance
“…The reflex testing procedure developed here provides a useful technique to differentiate abnormal CR activity in subjects with clinical signs of SCI spasticity and could be used to benchmark novel pharmacological or sensorimotor rehabilitation techniques designed to re-establish appropriate inhibitory modulation of CR function, thereby contributing to the better management of SCI spasticity. 40,42,66,70 DATA ARCHIVING There were no data to deposit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reflex testing procedure developed here provides a useful technique to differentiate abnormal CR activity in subjects with clinical signs of SCI spasticity and could be used to benchmark novel pharmacological or sensorimotor rehabilitation techniques designed to re-establish appropriate inhibitory modulation of CR function, thereby contributing to the better management of SCI spasticity. 40,42,66,70 DATA ARCHIVING There were no data to deposit.…”
Section: Resultsmentioning
confidence: 99%
“…41,[61][62][63] Specifically, the alpha-2 adrenoceptor agonist clonidine has been shown not only to restore inhibition of CR activity after SCI but also to facilitate TA muscle activation during gait, 64 supporting the hypothesis that adequate CR control improves residual motor function. We believe that careful CR testing should be used to benchmark standard and new pharmacological strategies for the control of the SCI spasticity syndrome, 63,65,66 while examining the wider effect of these therapies on residual muscle function after SCI 40,41 Limitations and future studies No correlation was identified between Pl-TA CR activity and the grade of hypertonia or spasm frequency, perhaps reflecting the poor sensitivity of the modified Ashworth and Penn scales to detect flexor reflex activity. Measurement of spasm activity in clinical studies is usually performed with the Penn scale, 35 but this scale often fails to correlate with the underlying pathophysiological mechanisms of SCI spasticity syndrome during movement, 7 or indeed with CR activity in general.…”
Section: Discussionmentioning
confidence: 99%
“…Even when people are resting, some areas of the brain are activated simultaneously, pulsating at the same frequency, which suggests that groups of neurons are communicating. This network is less active in a person with Alzheimer's (BALTHAZAR et al, 2014). The Unicamp group was able to distinguish with about 70% accuracy the images of brain activity in resting people with moderate symptoms of dementia, typical of healthy older people.…”
Section: Sgarbieri V C; Pacheco M T Bmentioning
confidence: 98%
“…However, in the short term it may be more realistic to think of ways to slow down the progress of brain injuries leading to Alzheimer's and prevent as much as possible the appearance of cognitive problems that gradually reduce the quality of life of patients. Details of the latest research on Alzheimer's mentioned above can be found in recent publications (MARTINS et al, 2005;MORI et al, 2008;ANDRADE-MORAES et al, 2013;LOURENÇO et al, 2013;BALTHAZAR et al, 2014).…”
Section: Sgarbieri V C; Pacheco M T Bmentioning
confidence: 99%
See 1 more Smart Citation